PENERAPAN MODEL STEAM DALAM PEMBELAJARANBIOLOGI SMA DI INDONESIA : Literature Review - Atip Nurwahyunani; Ipah Budi Minarti, Najwa Aulia, Aftakhul Rizkyana Meilani, Laili Fatrotul Munawaroh, Aliya Munasyifa (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This research aims to determine the influence of the Science, Technology, Engineering, Art, and Mathematics (STEAM) learning model on biology education in Indonesia. The method used in this study is a literature review to analyze the impact of the STEAM learning model. Data collection techniques involve documentation by searching relevant journals on this topic through Google Scholar, covering the past 5 years from 2019 to 2023. The analysis of the articles shows that the results of 10 articles prove that implementing the STEAM model in biology education positively influences students' critical thinking skills, creative thinking abilities, and learning outcomes.